2007
DOI: 10.1016/j.febslet.2007.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule inhibitors of type III secretion in Yersinia block the Chlamydia pneumoniae infection cycle

Abstract: Intracellular parasitism by Chlamydiales is a complex process involving transmission of metabolically inactive particles that differentiate, replicate, and re-differentiate within the host cell. A type three secretion system (T3SS) has been implicated in this process. We have here identified small molecules of a chemical class of acylated hydrazones of salicylaldehydes that specifically blocks the T3SS of Chlamydia. These compounds also affect the developmental cycle showing that the T3SS has a pivotal role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
91
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 22 publications
2
91
0
Order By: Relevance
“…We recently reported that salicylidene acylhydrazides (SAHs) act as inhibitors of the Yersinia pseudotuberculosis T3S (15,16). We further showed that the SAH variants INP0341 and INP0010 also inhibit Chlamydia growth and development, observations that have been corroborated by other groups (17,18,20,28). These findings suggest that T3S activity is essential for Chlamydia (22).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…We recently reported that salicylidene acylhydrazides (SAHs) act as inhibitors of the Yersinia pseudotuberculosis T3S (15,16). We further showed that the SAH variants INP0341 and INP0010 also inhibit Chlamydia growth and development, observations that have been corroborated by other groups (17,18,20,28). These findings suggest that T3S activity is essential for Chlamydia (22).…”
Section: Resultssupporting
confidence: 71%
“…Small-molecule screens performed by Kauppi et al identified salicylidene acylhydrazides (SAHs) as inhibitors of the Yersinia pseudotuberculosis T3S (15,16). Subsequent studies indicate that SAHs block Chlamydia growth but not entry into cells (17)(18)(19)(20)(21), which supports the prevalent notion that the T3S is essential during the middle and late stages of the Chlamydia developmental cycle (22). Subsequent studies indicate that secretion or localization of predicted T3S effectors is altered by SAHs (19,(23)(24)(25)(26).…”
mentioning
confidence: 48%
“…The targeting of nonvital bacterial processes decreases selection pressure, making mutation-based resistance to these therapies less likely (3). Investigations of the type III secretion system (T3SS), where promising molecules-some of which showed broad-spectrum activity for various bacterial pathogens-were identified through whole-cell-based high-throughput screens, have had success with this strategy (4)(5)(6).…”
mentioning
confidence: 99%
“…Although secretion activity has not been achieved, this promising approach could facilitate functional studies in a genetically tractable background. The use of chemical genetics has been attempted with chlamydiae by using small-molecule inhibitors of the NF-T3SS (86)(87)(88)(89) and CopN (30). Inhibition of infectivity by inhibitors of the NF-T3SS is reversed by exogenous iron, and chlamydiae that are resistant to the inhibitors contain mutations in hemG (90), making the link to T3S activity unclear.…”
Section: Future Prospectsmentioning
confidence: 99%